Glosas marginales de K. Rahner sobre el Concilio Vaticano II - Santiago Madrigal Terrazas, S. J. (Estudios eclesiásticos, 2005)
Karl Rahner’s theological reflections on the Second Vatican Council (1962-1965) run in parallel with a threefold psychological attitude: encouraging scepticism at its announcement; courage and sobriety during the event; a new Christian responsibility gained after the Council’s decisions. Reading through his epistolary notes, his speeches and discourses, and especially, his Theological Writings, this study aims to reconstruct the main issues of his theology on the Council, the impact of the concilial doctrines on the Church’s life, and the basic interpretation, typically Rahnerian, according to which the latest Council represents, above all, «a new beginning».